Research on spinocerebellar ataxia type 2 in Cuba: a bibliometric analysis - Velázquez-Pérez, Luis Clodoaldo; Ronda-Pupo, Guillermo Armando (Anales de la Academia de Ciencias de Cuba, 2025)
Introduction: Spinocerebellar Ataxia Type 2 is a hereditary neurodegenerative disorder. Over the past three decades, Cuban researchers have significantly advanced in the understanding of it. Their contributions span epidemiological surveillance, genetic and molecular research, biomarker discovery, clinical characterization, and therapeutic strategies. Objective: To provide a comprehensive bibliometric analysis of Spinocerebellar Ataxia Type 2 research in Cuba from 1996 to 2024. Methods: The study utilized data from 71 articles and reviews on Spinocerebellar Ataxia Type 2, accessed through the Web of Science database. VOS viewer software was employed to analyze keyword co-occurrence, co-author, and institutional collaboration networks. Co-word analysis identified thematic shifts, while co-authorship and institutional networks mapped collaboration patterns across national and international partners. Results: Results show an evolution in Cuban Spinocerebellar Ataxia Type 2 research from initial genetic studies focused on CAG repeat expansions in the ATXN2 gene to recent patient-centered clinical research, emphasizing diagnosis, biomarkers, and disease progression. Key institutions such as the Center for Research and Rehabilitation of Hereditary Ataxias, Cuban Academy of Sciences, and Cuban Center for Neurosciences emerged as primary research hubs, with longstanding collaborations involving German institutions. Newer partnerships with Latin American institutions, particularly the National Autonomous University of Mexico, reflect a regional focus on population-specific studies. Conclusions: The thematic progression in Spinocerebellar Ataxia Type 2 research reflects a shift toward translational and patient-focused approaches. Cuban-led Spinocerebellar Ataxia Type 2 research exemplifies successful international and regional collaboration, providing a model for tackling complex, population-specific health issues. Continued efforts in biomarker discovery, therapeutic development, and clinical applications are essential for advancing patient care and research impact in Spinocerebellar Ataxia Type 2. This bibliometric study offers strategic insights for guiding future research directions in Spinocerebellar Ataxia Type 2.